Effect of Earnings Management on Firm Value in Mining Companies Listed on the Indonesia Stock Exchange in the Period 2014-2018 - Mochammad Ridwan; Iman Sofian suriawinata; Rimi Gusliana Mais (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
Abstract—This study aims to determine the effect of Partial Earnings Management on Company Value. Using a sample of 85 in the 5 periods of 2014-2018 mining companies, this study found the effect of earnings management on negative company values significantly identified earnings management practices in mining companies that were opportunistic. The profitability control variable has no effect, leverage has no effect, while the size of the company affects the firm's value.